Nitric Oxide and L-Arginine Deficiency in Cystic Fibrosis - Grasemann, Hartmut; Ratjen, Felix (Current Pharmaceutical Design, 2012)
The concentrations of nitric oxide are decreased in airways of patients with cystic fibrosis. The reasons for this nitric oxide deficiency are incompletely understood but may include reduced production from nitric oxide synthases due to decreased expression, the enzymes in airway epithelial cells, reduced availability of L-arginine, the substrate for nitric oxide synthases, and the presence of endogenous inhibitors of the enzymes in the airways. As nitric oxide plays a role in a number of important physiological processes in the lung including host defense against pathogens such as Pseudomonas aeruginosa, inflammation and the regulation of vascular and broncho motor tone, the lack of nitric oxide may contribute to lung disease in cystic fibrosis patients. Therapeutic interventions aiming to correct the nitric oxide deficiency in the cystic fibrosis airways are therefore currently being explored as new therapies for these patients.
Keywords: airways